Research of migration processes in electronic social networks - A. A. Grebenyuk; A. A. Subbotin (Цифровая социология)
The article сarries out an analysis of the practices of using electronic social networks (Facebook, Twitter, Vkontakte, etc.) in the study of migration processes. The paper shows how alternative to traditional sources (administrative, surveys) data allow us to form an up-to-date idea of the spatial-temporal and socio-demographic characteristics of migration. The authors study the integration of migrants in destination countries, including difficulties of assimilation and identity preservation, geography of migration flows, migration due to natural disasters and political reasons, intellectual and labour migration. The specificity of the data generated by social networks is that they cover the entire population and are produced in real time.The paper highlights the search for the necessary information using the means of platforms – advertising plugins, geolocation in posts and information directly collected from users, the functioning of certain communities, published comments. The study also gives important methodological features, the success of the results of any research conducted through the analysis of electronic social networks depends on the consideration of which. The problem of the information obtained with their help lies in such limitations as accessibility (technical features of specific platforms), representativeness (insufficient development of statistical techniques for evaluation) and variability of user preferences. In conclusion, the authors conclude about the prospects of using digital mass communication media in the study of migration processes.The scientific and practical significance of the research paper lies in the fact that it complements the literature on the topic under consideration, being the first systematic review of it in the Russian language, and also provides recommendations on the use of the information obtained.